VISUALIZATION OF RISKS ON THE BASIS OF PYROSIM SOFTWARE - PRAUZNER, Tomasz (Trends in education, 2014)
The article presents an analysis of the simulation software PyroSim and results obtained in the scientific research result of the modeling, mathematical calculation and visualization of the risk of fire in an exemplary residential object. The environmental issue is one of the key issues discussed during the classes in the direction of Safety Engineering, conducted by the Institute of Technical Education and Safety Jan Dlugosz University in Czestochowa.
Keywords: PyroSim; environmental protection; teaching; visualization and simulation of fire.